Pedal and crank kinetics in uphill cycling - Caldwell, G. E.; Li, L.; McCole, S. D.; Hagberg, J. M. (Journal of Applied Biomechanics, 1998)
Alterations in kinetic patterns of pedal force and crank torque due to changes in surface grade (level vs. 8% uphill) and posture (seated vs. standing) were investigated during cycling on a computerized ergometer. Kinematic data from a planar cine analysis and force data from a pedal instrumented with piezoelectric crystals were recorded from multiple trials of 8 elite cyclists. These measures were used to calculate pedal force, pedal orientation, and crank torque profiles as a function of crank angle in three conditions: seated level, seated uphill, and standing uphill. The change in surface grade from level to 8% uphill resulted in a shift in pedal angle (toe up) and a moderately higher peak crank torque, due at least in part to a reduction in the cycling cadence. However, the overall patterns of pedal and crank kinetics were similar in the two seated conditions. In contrast, the alteration in posture from sitting to standing on the hill permitted the subjects to produce different patterns of pedal and crank kinetics, characterized by significantly higher peak pedal force and crank torque that occurred much later in the downstroke. These kinetic changes were associated with modified pedal orientation (toe down) throughout the crank cycle. Further, the kinetic changes were linked to altered nonmuscular (gravitational and inertial) contributions to the applied pedal force, caused by the removal of the saddle as a base of support.